PERBANDINGAN FAKTOR RISIKO MALARIA DENGAN KEJADIAN MALARIA DI DESA TANJUNG SATAI DAN DESA KEMBOJA KABUPATEN KAYONG UTARA - Natalia, Diana; Raharjo, Widi; Syafril, Muhammad (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
Background: Malaria is the most important parasitic infections in the world, including in Indonesia. Kabupaten North Kayong is one of malaria endemic areas in West Kalimantan. Tanjung Satai village is one of the village that has the highest Annual Parasite Incidence (API) with number 15,89 per 1 000 at Kabupaten North Kayong. The incidence of malaria is influenced by the level of knowledge, individual behavior, the physical condition of the house and the house environment Objectives: To find out the comparison between the level of knowledge, individual behavior, the physical condition of the house and the house environment with the incidence of malaria in Tanjung Satai village and Kemboja village, Kabupaten North Kayong. Methods: This research was case control design. Cases were residents who had positive malaria in 2011 and controls were residents who have never had malaria. Bivariate analysis used Chi-Square test. Results: The number of samples in this research were 110 respondents (55 of case respondents and 55 of control respondents). The independent variables that influenced the incidence of malaria are the level of knowledge (p=0,007; OR=2,88), using the mosquito net (p=0,039; OR=3,09), the existence of bushes (p=0,001; OR=0,27) and the existence of stagnant water (p=0,016; OR=0,37). The independent variables that did not influence the incidence of malaria are using mosquito repellent, installing wire net, and the density of house wall. Conclusion: The lower level of knowledge, not using the mosquito net, the existence of bushes and the existence of stagnant water have risk 2,88; 3,09; 0,27; 0,37 times to get malaria.